High‐Performance Cadmium‐Free Blue Quantum Dot Light‐Emitting Devices with Stepwise Double Hole‐Transport Layers - Zhiqi Luo; Yongshen Yu; Kaiyu Yang; Lihua Lin; Jintang Lin; Tailiang Guo; Hailong Hu; Fushan Li (Advanced Electronic Materials, 2023)
Abstract ZnSe/ZnS core/shell quantum dots (QDs) are environmental‐friendly blue light‐emitting material, which can easily achieve deep blue emission upon external excitation. However, its deep valence band (VB) and numerous defect states remain handicap to realize sufficient performance of quantum dot light‐emitting diodes (QLEDs). In this work, high‐performance cadmium‐free ZnSe/ZnS QLEDs by constructing a double organic hole‐transport layer (HTL) to obtain carrier balance are presented. The double HTLs, which consist of poly(9,9‐dioctylfluorene‐co‐N‐(4‐butylphenyl)diphenylamine) (TFB) and 2,7‐dioctyl[1]benzothieno[3,2‐b][1]benzothiophene (C8‐BTBT), can suppress the accumulation of electrons between the HTL and the emissive layer (EML), leading to more hole and electron recombination luminescence in QD layer. In addition, the C8‐BTBT layer is conducive to improve the uniformity of QDs film. Thus, the resulting device achieves an external quantum efficiency of 7.23% with TFB/C8‐BTBT double HTLs, which is almost 150% higher than that of traditional devices based on a single hole‐transport layer (4.84%). The authors anticipate that these results can provide a guidance for the optimization of cadmium‐free blue QLEDs.